DEVELOPMENTAL DIDACTICS FOR PROFESSIONAL SKILLS AND UNIVERSITY EDUCATION (Proceedings of the International Conference on Education, 2021)
The objective of the article was to determine the effect of developer didactics in university education, related to teaching, learning and training of graduate professionals, strengthening their identity and empathy with social reality. University education must prepare citizens, its objective is to prepare, train and educate. In this process, skills, abilities, capacities and competencies are acquired to solve society's problems through research, scientific knowledge, which is used to solve them. The developer didactics allowed to overcome the difficulties of the educational teaching process, which was based on constructivism that allowed affirming learning. The methods of learning based on problems and cooperative were applied. The sample consisted of 121 undergraduate students, distributed in 3 time groups. The quality of the model for the proposed learning-teaching process allowed the achievement of significant knowledge. The evaluation was participatory and innovative in nature, not directive; the contents were evaluated at the level of knowledge, procedures and attitudes, within the framework of the professional profile and the exercise of their professional career. The research showed that through the application of developer didactics, general, professional and specialized competences were significantly promoted in students. This process was materialized in an evaluation of a participatory nature, of a continuous nature in the subject, being a significant achievement, with an average of more than 17. Therefore, the approach based on the development didactics in a curriculum by competencies, is highly significant and representative in the three investigated samples.
Keywords: Developer didactics; socioformative; professional competences; pedagogical-didactic method; educational teaching process; education